Improvements in mental health associated with increased electronic communication and deterioration in physical health in adults aged 50+ during the COVID-19 pandemic - Shay Musbat; Inbal Reuveni; Racheli Magnezi (Frontiers Media S.A., 2024)
BackgroundPrevious studies have documented changes in physical health, mental health and social parameters during COVID-19. At the same time, there are no comprehensive analyses of these parameters designed as longitudinal studies on large-scale older populations before and during the pandemic.ObjectiveThis longitudinal study aims to provide a quantitative analysis of the COVID-19 impact on the physical, mental, and social parameters in adults aged 50 and older before, in the early stages, and during the COVID-19 pandemic.MethodsThe data for this study were collected from three waves of the Survey of Health, Ageing and Retirement in Europe (SHARE), a supranational longitudinal database: pre-COVID (October 2019-March 2020), early-COVID (June-September 2020), and during-COVID (June-August 2021). The sample included 31,526 individuals, compared across the three-time points through nonparametric group comparison tests.ResultsPhysical health was subjectively rated as poorer in the during-COVID wave compared to the pre-COVID wave. Additionally, the number of illnesses or health conditions reported in the during-COVID wave was significantly higher than in the pre-COVID wave, with the biggest increases registered for cardiovascular diseases. The results also show that employment and overall social contact decreased while loneliness increased over time. Unexpectedly, mental health issues, such as sadness or depression and trouble sleeping, decreased significantly in the COVID waves compared to the pre-COVID wave. The analysis of two additional pre-COVID waves (2015, 2017) revealed that poorer pre-COVID mental health reflected in high values of sadness or depression and trouble sleeping was not an isolated peak but represented a typical baseline. The positive influence on the individuals' mental health during COVID-19 was found to be electronic communication, which showed higher values than face-to-face communication and lowered the odds of sadness or depression.ConclusionFuture policies should thus consider the positive impact of electronic contacts on mental health to promote overall health in adults aged 50 and older.